2017
DOI: 10.1021/acs.est.6b05832
|View full text |Cite
|
Sign up to set email alerts
|

Black Carbon Sources Constrained by Observations in the Russian High Arctic

Abstract: Understanding the role of short-lived climate forcers such as black carbon (BC) at high northern latitudes in climate change is hampered by the scarcity of surface observations in the Russian Arctic. In this study, highly time-resolved Equivalent BC (EBC) measurements during a ship campaign in the White, Barents, and Kara Seas in October 2015 are presented. The measured EBC concentrations are compared with BC concentrations simulated with a Lagrangian particle dispersion model coupled with a recently completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 40 publications
2
33
0
5
Order By: Relevance
“…According to a related study by Huang and Fu (2016), Russia contributes 57 % to the global BC emissions from gas flaring. Underestimation of modelled atmospheric concentrations compared to observations from the Barents and Kara seas was recently also reported by Popovicheva et al (2017), although the underestimation was relatively small.…”
Section: Model Deviation From Snow Ec Measurements and Region-specifisupporting
confidence: 61%
See 1 more Smart Citation
“…According to a related study by Huang and Fu (2016), Russia contributes 57 % to the global BC emissions from gas flaring. Underestimation of modelled atmospheric concentrations compared to observations from the Barents and Kara seas was recently also reported by Popovicheva et al (2017), although the underestimation was relatively small.…”
Section: Model Deviation From Snow Ec Measurements and Region-specifisupporting
confidence: 61%
“…However, in the most recent assessments of BC of the higher Arctic (Popovicheva et al, 2017;Winiger et al, 2017), it was shown that ECLIPSE captures levels of BC quite well, whereas FLR emissions might have a smaller impact in the central Siberian Arctic (Tiksi) than previously estimated. Surprisingly, the average contribution from BB in lower latitudes was extremely low in all western Siberia (Figs.…”
Section: Model Deviation From Snow Ec Measurements and Region-specifimentioning
confidence: 87%
“…Only small contributions come from other sources (gas flaring, power plants, and open fires). Measurements and model‐based source apportionment of BC in the Kara Strait pointed toward the importance of gas flaring emissions from the Yamal‐Khanty‐Mansiys and Nenets‐Komi regions (Popovicheva et al, ). In the White Sea, biomass burning from the midlatitudes, surface transportation, and residential and commercial combustion in Central and Eastern Europe are important sources of BC (Popovicheva et al, ).…”
Section: Local Arctic Air Pollutant Emissionsmentioning
confidence: 99%
“…Measurements and model-based source apportionment of BC in the Kara Strait pointed toward the importance of gas flaring emissions from the Yamal-Khanty-Mansiys and Nenets-Komi regions (Popovicheva et al, 2017). In the White Sea, biomass burning from the midlatitudes, surface transportation, and residential and commercial combustion in Central and Eastern Europe are important sources of BC (Popovicheva et al, 2017). Evans et al (2015) focused on BC emissions from diesel sources on the Kola Peninsula with special emphasis on Murmansk, the largest city north of 60°N.…”
Section: 1029/2018ef000952mentioning
confidence: 99%
“…Intercalibration with the AE33 aethalometer (Magee Scientific) was performed at the GAW station of N.S.C.R. Demokritos (Athens), simultaneously with long-term measurements of ambient aerosols, as described elsewhere (Popovicheva et al, 2017). The level of uncertainty (1-sigma) of EBC measurements is 30 ng m -3 for 6-minute integrated sampling.…”
Section: Instrumentation and Samplingmentioning
confidence: 99%